A pediatric case of anti-GABABR encephalitis: case report and literature review - Fu, Junxian; Jia, Kairu; Li, Tianxia; Qiao, Zhidong; Jia, Yuexin; Yang, Xiaofan; Pan, Hao; Zhao, Lu; Li, Peirong; Zan, Manjie; Yang, Guanglu (Frontiers in Pediatrics, 2025)
Background and objectiveThis study aims to analyze the clinical characteristics of anti-GABABR encephalitis in pediatric patients. Due to its rarity and diagnostic challenges in children, we compare clinical features between adult and pediatric cases.Materials and methodsUsing the key words “anti-GABABR encephalitis, children, autoimmune encephalitis, limbic encephalitis”, we conduct a comprehensive literature review of all studies related to anti-GABABR encephalitis published from January 2010 to January 2024. A total of 207 cases are identified globally, including 14 pediatric cases.ResultsWe report a case of an 8-year-and-6-month-old child with anti-GABABR encephalitis presenting with abnormal mental behavior (irritability, hallucinations), sleep disorders, and paroxysmal involuntary limb movements. Serum anti-GABABR antibodies were positive, and clinical symptoms improved significantly after corticosteroid treatment. Analysis reveal that children presented with mental/behavioral abnormalities as the initial symptom (85.71%), while adults presented with epileptic seizures as the initial symptom (76.71%). Main symptoms include epilepsy in adults (78.24%) and sleep disorders (26.67%) and involuntary limb movements (33.33%) in children. Neuroimaging shows higher involvement of the basal ganglia (55.56%), cerebellar hemispheres (22.22%), and brainstem (22.22%) in children compared to adults. Video electroencephalogram (EEG) analysis indicates more frequent abnormal EEG in adults, but epileptic waves are more common in children with abnormal EEG. Cerebrospinal fluid (CSF) cytology is not specific, with mild lymphocytic increases (adults 57.98% vs. children 33.33%, P = 0.2054). Despite higher prodromal fever rates in children (66.67% vs. 23.44%, P = 0.0228), they respond better to immunotherapy. No tumor-related issues are observed in pediatric cases, contrasting with 58.09% tumor comorbidity in adults.ConclusionsThis study suggests that the clinical phenotypes of anti-GABABR encephalitis in children and adults may differ: children are more likely to present with mental and behavioral abnormalities (the initial symptom trend), sleep disorders and involuntary movements (the main symptoms), and their brain imaging is more likely to involve regions such as the basal ganglia and brainstem, and they respond better to immunotherapy. Notably, due to the small sample size of pediatric cases (n = 15) compared to adult cases (n = 193), these comparative findings should be interpreted with caution despite the statistical significance indicated by P-values. However, long-term follow-up remains essential.